Hukum Tes Swab saat Berpuasa untuk Deteksi Covid-19 pada Bulan Ramadan (Studi Fatwa MUI No. 23 tahun 2021): Law for Swab Tests while Fasting for Detection of Covid-19 in the Month of Ramadan (Study of MUI Fatwa Number 23 of 2021) - Nur Annisa Anzar; Ahmad Syaripudin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to find out and analyze Fatwa of the Indonesian Ulema Council number 23 in 2021 regarding the law on implementing swab tests while fasting to detect the presence of Covid-19 during the month of Ramadan. The problems that the author raises in this research are: First, what is the description of the swab test procedure. Second, what is the Fatwa of the Indonesian Ulema Council regarding the law regarding swab tests when fasting to detect Covid-19. This type of research is library research, with a qualitative descriptive method and using a normative juridical approach and a conceptual approach. The research results found were as follows; First, the swab test is part of the PCR (Polymerase Chain Reaction) test which is used to get a diagnosis of whether someone is infected with the Covid-19 virus or not and is one of the tests that is considered to have the most accurate results. The swab test is carried out by inserting a device in the form of Dacron/rayon into the throat through a person's mouth (oropharynx) and nose (nasopharynx). Second, Fatwa of the Indonesian Ulema Council number 23 in 2021 stipulates that swab tests may be carried out and do not break the fast, in this case it is one of the health protocols during the Covid-19 pandemic in order to break the chain of transmission of Covid-19, including during the month of Ramadan and Muslims who are fasting are allowed to take a Swab test to detect Covid-19.